Clinical assessment of efficacy and safety of DDAVP - Miesbach, W.; Krekeler, S.; Dück, O.; Llugaliu, B.; Asmelash, G.; Schüttrumpf, J.; Alesci, S.; Großmann, R. (Hämostaseologie, 2010)
The efficacy of DDAVP (1-deamino-8-D-argi-nine-vasopressin, desmopressin) in mild haemophilia A and von Willebrand disease (VWD) has been established and the use of this well tolerated drug has become clinical routine. In case of increased fluid intake and based on very rarely occurring hyponatraemia, the indication of administration of DDAVP intravenously (i. v.) has to be performed diligently in elderly patients and in children below the age of five years. Aim, patients: Due to clinical practice we were interested in finding prospective parameter potentially correlating with adverse reactions of DDAVP and initiated this study. From 2007 to 2008, we included 49 patients suspicious to suffer from mild haemophilia A (n = 1) or VWD (n = 48) and investigated efficacy and safety of DDAVP after intravenous administration (mean: 0.29 ± 0.032 μg/kg body weight). They underwent clinical and laboratory investigation and were questioned with regard to potential adverse reactions immediately and three days after administration of DDAVP.: Results, conclusion: Most adverse reactions were mild and no serious adverse drug reactions were either observed or reported by the subjects. We identified significant changes of heart rate, blood pressure and leucocytes after conduct of the DDAVP test. The value of these findings has to be investigated in later prospective randomized studies. Further research on identification of prospective parameter is currently ongoing.
Keywords: Desmopressin; DDAVP; safety; adverse reactions; mild hemophilia A; von Willebrand disease